The benefit of taxane-based therapies over fluoropyrimidine plus platinum (FP) in the treatment of esophageal cancer: a meta-analysis of clinical studies - Wang T; Yu J; Liu M; Chen Y; Zhu C; Lu L; Wang M; Min L; Liu X; Zhang X; Gubat JA; Chen Y (Dove Medical Press, 2019)
Tao Wang,1,* Jie Yu,1,* Min Liu,1,* Yanliang Chen,1 Caiyun Zhu,1 Lin Lu,2 Mingzhu Wang,2 Lingfeng Min,3 Xinxin Liu,4 Xizhi Zhang,1 Johannes A Gubat,5 Yong Chen1 1Department of Medical Oncology, Clinical Medical College, Yangzhou University, Yangzhou, Jiangsu, China; 2Department of Medical Oncology, Dalian Medical University, Dalian, Liaoning, China; 3Department of Respiratory Medicine, Clinical Medical College, Yangzhou University, Yangzhou, Jiangsu, China; 4Department of Gastrointestinal Surgery, Clinical Medical College, Yangzhou University, Yangzhou, Jiangsu, China; 5Division of Oncology and Pathology, Department of Clinical Sciences, Lund University, Lund, Sweden *These authors contributed equally to this work Purpose: Fluoropyrimidine plus platinum (FP) is currently the standard treatment for esophageal cancer (EC). In recent years, taxane-based chemotherapy has also been used and has shown good efficacy in EC. This study aims to investigate the advantages of taxane-based over FP chemotherapy, as well as discuss its drawbacks, in the treatment of EC. Patients and methods: A literature search was done for studies comparing clinical outcomes between taxane-based and FP chemotherapy in EC. Pooled analyses were performed to compare the efficacy and grade 3/4 adverse events in patients who received neoadjuvant chemotherapy (NACT), neoadjuvant chemoradiotherapy (NACRT), or definitive chemoradiotherapy (dCRT). Subgroup analyses were also conducted in esophageal squamous cell carcinoma (ESCC). Results: Thirty-one studies with a total of 3,912 patients were included in the analysis. Better long-term survival was found in patients who received taxane-based NACT (progression-free survival (PFS): pooled HR=0.58, P=0.0008; and overall survival (OS): pooled HR=0.50, P<0.00001) and dCRT (PFS: pooled HR=0.75, P<0.0001). In NACRT, taxane-based treatment and FP showed similar efficacy. In ESCC patients, taxane-based treatment showed better OS (NACT: pooled HR=0.57, P=0.02; NACRT: pooled HR=0.51, P=0.03; and dCRT: pooled HR=0.73, P<0.0001) than FP chemotherapy. Furthermore, taxane-based therapy also showed a better short-term response (complete response (CR), objective response rate (ORR), disease control rate (DCR), or pathologic complete response (pCR). However, taxane-based therapy was significantly correlated with a higher incidence of grade 3/4 leukopenia, neutropenia, and diarrhea. Conclusion: Compared to FP, taxane-based therapy produced better clinical response and outcomes in EC patients receiving NACT or dCRT, and in all types of therapy in patients with ESCC. Taxane-based treatment is associated with more frequent toxicity. Keywords: digestive cancer, chemotherapy, survival, clinical cancer research